Osmanlı basınında iktisadi tefrikacılık (Hazine-i Evrak Dergisi): Mahmud Celaleddin’in ekonomi politiği ile Suphi Paşa’nın layihası - Demir, Kenan (Karadeniz Teknik Üniversitesi, 2020)
Osmanlı Devleti’nde dergiler bir okul vazifesini icra etmiş ve dergilerin yayım politikasının önemli unsurlarından biri de halkı eğitmek olmuştur. Dergilerin halkı bilgilendirdiği konulardan biri de iktisadi meselelerdir. Osmanlı Devleti’nde modern iktisat düşüncesinin halka yayılmasında önemli aracılardan biri de dergiler olmuştur. Halk dergiler vasıtasıyla ekonomi ilmiyle tanışmış ve bu ilmin kurallarını dergilerde çıkan ekonomi konularındaki yazılar ile ekonomi kitap tefrikalarından öğrenmiştir. Dergilerde birçok iktisadi kitabın tefrikası yapılmıştır. Yayımlanan kitapların dilinin basit olması ve soru-cevaplı yani karşılıklı konuşma şeklinde verilmesi bu tefrikalarla amacın iktisat ilminin öğretilmesi olmuştur. II. Abdülhamit döneminin önemli bir fen ve edebiyat dergisi olan Hazine-i Evrak dergisinde de iktisatla alakalı iki kitabın tefrikası yapılmıştır. Kitaplardan biri modern iktisadi anlayışla yazılmış kitabın bir kısmının “Ekonomi Politik: İlmi Emval-i Milliye” başlığıyla verilmesidir. Diğeri de Suphi Paşa’nın 1865’te padişaha sunduğu geleneksel görüş doğrultusunda yazılan maliyeyle ilgili risalesidir. Bu iki tefrika ile Hazine-i Evrak dergisi okurlarına ekonomiyle ilgili konularda halkı eğitmeyi amaçlamıştır. Çalışmada bu iki tefrikanın içeriği verilerek derginin ekonomi anlayışı aktarılmıştır.

In the Ottoman State, magazines performed a school duty and one of the important elements of the publication policy of the magazineswas to educate the public.One of the issues that magazines inform the public is economic issues. Magazines have been one of the important mediators in the spread of modern economic thought in the Ottoman Empire. The people got acquainted with the science of economics through magazines and learned the rules of this science from the books of economics through articles on economics published in magazines. Many magazines have been serialized in magazines. The language of the published books is simple and it is given in the form of question-answer, that is, mutual speech, and the aim is to teach the science of economics. In the journal Hazine-i Evrak, an important science and literature journal of the II. Abdulhamid era, two books related to economics were also serialized. One of the books is that a part of the book written with a modern economic understanding is given under the title of "Political Economy: İlm-i Emval-i Milliye". The other one is the treatise about the finance written by Suphi Pasha in line with the traditional view of the sultan in 1865. With these two serials, Hazine-i Evrak magazine aimed to educate the public on economic issues on their readers. In this study, the concept of economy of the magazine is given by giving the contents of these two serials.
Economic communicatıon in the Ottoman Press (Hazine-i Evrak Magazine): Mahmud Celaleddin's economic policy and layiha of Suphi Pasha
Keywords: Suphi Paşa; Mahmud Celaleddin; Osmanlı İktisat Düşüncesi; Suphi Paşa; Mahmud Celaleddin; Ottoman Economic Thought